The Eliminations of Intra-Group Accounts, Unachieved Internal Results and Dividends - Corina-Graziella BÂTCĂ-DUMITRU (CECCAR Business Review, 2021)

(untitled)
The aim of this paper is to present, according to the Order of the Minister of Public Finance No. 1802/2014 for the approval of the Accounting regulations regarding the individual annual financial statements and consolidated annual financial statements, as subsequently amended and supplemented, the rules for eliminating intra-group accounts for transactions undertaken between companies consolidated through the global integration method and the equity method, the rules of eliminating the unachieved internal results when these are significant, as well as the types of eliminations of internal results that impact the consolidated result: dividends eliminations, the elimination of the result related to initial and final inventories, the result generated by the sale of long term assets and the valuation allowances for inventories and receivables.